Roman traces in Germania magna: New thermoluminescence and pIRIR290 data from a lime kiln at Bergisch Gladbach, Germany. (19th November 2018) - Zander, A.; Strebler, D.; Classen, E.; Rethemeyer, J.; Brückner, H.
Abstract : The applicability of a post‐infrared infrared stimulated luminescence (pIRIR290 ) protocol and two different thermoluminescence (TL) protocols—a single aliquot regeneration (SAR) and a multiple aliquot additive dose (MAAD)—was tested on six polymineral fine‐grain (4–11 μm) samples extracted from the wall remains of a Roman lime kiln and a Roman roof tile. These remains had been excavated close to Bergisch Gladbach, which was at that time part of Germania magna. For the pIRIR290 measurements, no dependence of D e on first‐stimulation temperature was detectable, and the standard first stimulation temperature at 50°C was adopted. Fading tests and dose‐recovery tests were made for all samples. Background subtracted glow curves were recorded up to 480°C for TL after a preheat of 220°C for 120 s. A ‐values were determined for all TL and pIRIR measurements. The results for all three protocols were fairly consistent, and TL and pIRIR290 protocols are shown to be suitable to estimate reliable equivalent doses for the fired kiln walls. The resulting ages are in agreement with the expected time range—Roman Iron Age—and with independent age control provided by radiocarbon ages of animal bones and charcoal from the firing chamber. Abstract : Highlights: A Roman lime kiln and surrounding sediments were successfully dated using both thermoluminescence (TL) and post‐infrared infrared stimulated luminescence (pIRIR).